INTERPRETATION OF THE AMIR TEMUR ANTHROPONYM IN THE CONTEXT OF HISTORICAL AND ARTISTIC WORKS - Jabborov, Khojamurod; Muminova, Nilufar; Muminova, Nilufar (International Journal of Psychosocial Rehabilitation, 2020)
In the history of Uzbek statehood, the merits of the great Amir Temur and the Temuri dynasty are incomparable, vast and incomparable. The activity of the Temuri dynasty, which has been in power since the third quarter of the XIV century until the end of the nineteenth century, is closely connected with the name of the great statesman Amir Temur, who has left an indelible mark in the history of our country and the world. The creative and military activities of Amir Temur in the socio-political, educational and spiritual spheres serve as the most important guide for the modern independence.